Heart disease and breast cancer perceptions: Ethnic differences and relationship to attentional bias. Issue 2 (June 2016) - Berry, Tanya R; Curtin, Kimberley D; Courneya, Kerry S; McGannon, Kerry R; Norris, Colleen M; Rodgers, Wendy M; Spence, John C
Differences in perceptions of susceptibility, seriousness, and fear of heart disease and breast cancer were examined and related to attentional bias for disease-related words among Canadian women of various ethnic ancestry. Women ( n  = 831) completed an online survey, and 503, among them, also completed an attentional bias task. Perceived seriousness of breast cancer predicted attentional bias for breast cancer in women of South Asian ancestry. Lifestyle behaviors were related to breast cancer attentional bias in women with British ancestry. Understanding relationships between modifiable risk factors, disease risk perceptions, and attentional biases among different ethnic groups can help create targeted promotional campaigns.